2021
DOI: 10.29227/im-2021-02-12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Harmonics on the Working Efficiency of a 6/1.2 kV Transformer in a Pit Mine

Abstract: Explosion-proof transformers 6/1.2 kV is important electrical equipment responsible forsupplying electricity in underground mine electrical networks. A failure of this transformer will cause aninterruption in the power supply and loss of safety in underground mining. Usually, explosion-prooftransformers in underground mine electrical networks are designed and manufactured to work with idealparameters such as sinusoidal currents, and the network structure is symmetrical. However, today inunderground mine electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The three-phase explosion-proof transformer with power of 630-kVA and voltage 6/1.2 kV is the type used quite commonly in the underground mine power network. Parameters of it are presented in Table 2 [11]. This is the main research object of the paper.…”
Section: Simulation Model For a Three-phase Explosion-proof Transformermentioning
confidence: 99%
See 1 more Smart Citation
“…The three-phase explosion-proof transformer with power of 630-kVA and voltage 6/1.2 kV is the type used quite commonly in the underground mine power network. Parameters of it are presented in Table 2 [11]. This is the main research object of the paper.…”
Section: Simulation Model For a Three-phase Explosion-proof Transformermentioning
confidence: 99%
“…Research on the effect of harmonics on transformer performance in underground mines has shown that the current flowing through the transformer is not sinusoidal, causing overload for the transformer even when operating properly with design specifications [11]. Voltage unbalance causes the peak efficiency working point to shift and transformer efficiency to decrease under all load cases [3].…”
Section: Introductionmentioning
confidence: 99%
“…This encourages Vietnam's coal mines to operate with high frequency [2]. Nowadays, Vietnam's mining is getting deeper and deeper, and the degree of mechanization is increasing, making electricity consumption even bigger [4,5]. The efficient use of electricity to reduce the power consumption per ton of mined coal is of great significance in improving labor productivity, reducing environmental emissions, and moving towards sustainable socio-economic development of the Government of Vietnam in the current period [1].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing degree of mechanization, power electronic converters are gradually being used at all stages of underground mining. They are responsible for regulating the working process of the motor or improving the power quality of the mine power network [2][3][4].…”
Section: Introductionmentioning
confidence: 99%